Direct 40Ar/39Ar dating of Late Ordovician and Silurian brittle faulting in the southwestern Norwegian Caledonides. (4th August 2016) - Scheiber, Thomas; Viola, Giulio; Wilkinson, Camilla Maya; Ganerød, Morgan; Skår, Øyvind; Gasser, Deta
Abstract: Structural data as well as U–Pb zircon and 40 Ar/ 39 Ar biotite and muscovite ages were collected from the Rolvsnes granodiorite in western Norway. The granodiorite intruded at c . 466 Ma, cooled quickly and escaped later viscous deformation. Brittle top‐to‐the‐NNW thrust faults (Set I) and WNW–ESE striking dextral strike‐slip faults (Set II) formed in a NNW–SSE transpressional regime. 40 Ar/ 39 Ar dating of synkinematic mica from both sets reveals a c . 450 Ma (Late Ordovician) age of faulting, which constrains early‐Caledonian brittle deformation. Set I and II faults are overprinted by a set of lower‐grade, variably oriented chlorite‐ and epidote‐coated faults (Set III) constraining WNW–ESE shortening. A lamprophyric dyke oriented compatibly with this stress field intruded at c . 435 Ma (Silurian), indicating that Set III formed at the onset of the Scandian Baltica–Laurentia collision. The preservation of Caledonian brittle structures indicates that the Rolvsnes granodiorite occupied a high tectonic level throughout the Caledonian orogeny.